Pendampingan Branding Usaha dan Manajemen Keuangan dalam Rangka Pendirian Unit Usaha Mandiri Kantin Pimpinan Cabang Pemuda Muhammadiyah Kasihan, Bantul - Puspita Dewi Wulaningrum; Andreani Hanjani; Linda Kusumastuti Wardana (Jurnal Pengabdian Pada Masyarakat, 2020)
BUSINESS BRANDING AND FINANCIAL MANAGEMENT ASSISTANCE IN THE ESTABLISHMENT CANTEEN OF THE INDEPENDENT BUSINESS UNIT HEAD OF MUHAMMADIYAH YOUTH BRANCH OF KASIHAN, BANTUL. The Head of the Muhammadiyah Kasihan Youth Branch (PCPM Kasihan) is one of Muhammadiyah's autonomous organizations. Muhammadiyah Youth became the hope of Muhammadiyah as the successor of the movement which was expected to have expertise and independence so that later it would become a qualified successor and master all fields that became the pillars of Muhammadiyah, including the pillars in the economic field. PCPM Kasihan is actually an autonomous organizations that is quite active and developing in the Pity branch especially in the management of organizations, except that the productive economic sector has not been touched, even though the field needs to be developed to create organizational independence. Based on these problems, the idea emerged to establish a canteen as an independent PCPM Kasihan business unit engaged in the economy. For the initial establishment of a business unit, proper branding planning is needed in order to be able to attract consumers. In addition, knowledge related to financial management is also needed so that the income and expenditure of the funds obtained can be controlled. Therefore, the method used in this PKM is by facilitating the making of branding for marketing strategies as well as training and mentoring in carrying out planning, financial recording and financial reporting. The implementation of this service resulted in the initial branding for business establishments in the form of neon boxes and container boxes. While the implementation of service for the management aspects, namely training and assistance in financial records needed in running a business later.